Evaluation of Effects of Aqueous Extract of Ficus capensis (thunb.) leaves in Adult Albino Rats - Chikwendu, Justina Ndirika; Nwamarah, Joy Ugo; Uchegbu, Vivian A. (Asian Journal of Biological and Life Sciences, 2015)
The study evaluated the effect of aqueous extract of Ficus capensis leaves in albino rats. The study specifically investigated the effect of the extract on some liver enzymes (aspartate aminotransferase (AST) and alanine aminotransferase (ALT)) activities, the packed cell volume (PCV), total white blood cell count and differential white blood cell count of the rats. Effect of the extract on serum urea and creatinine levels were also studied. Twenty-five (25) adult male albino rats were used for the study. The extract was prepared and the solution was filtered and fed the rats (25%, 50%, 75% and 100%) of the filtrates. Tap water was fed to the control rats. All the parameters were assessed using standard methods. One –way analysis of variance was used to obtain the means from the biochemical result. The means obtained were separated using Duncan Student Multiple Range Test. Results obtained showed that ALT, AST and creatinine levels of the rats that were fed 100% Ficus capensis extract were significantly higher than those that were fed diluted Ficus capensis extract. Hence, this had adverse effects on the liver cells of the rats. Also result showed that there is improved nutritional status and immunity when properly diluted
Keywords: Albino rats; Aqueous extract; Effects; Ficus capensis